2019
DOI: 10.1002/jmv.25444
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human parvovirus B19 among measles and rubella suspected patients from Cuba

Abstract: Between September 2014 and December 2015, 298 sera from rash and fever patients from all over Cuba were investigated for specific IgM antibodies against measles, rubella, dengue, human parvovirus B19 (B19V) and human herpesvirus 6 (HHV6) using a commercial enzyme-linked immunosorbent assay kits. B19V IgM positive and equivocal samples were investigated by a polymerase chain reaction and genotyping. No measles, rubella or dengue cases were detected. HHV6-IgM antibodies were confirmed in 5.7% and B19V-IgM antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 16 publications
1
19
2
Order By: Relevance
“…Nevertheless, the identification of ancient B19V in a Colonial context is noteworthy considering several recent reports reveal that measles-like cases were actually attributable to B19V (De Los Ángeles Ribas et al, 2019;Rezaei et al, 2016) or rubella (Anderson et al, 1985;Davidkin et al, 1998;De Los Ángeles Ribas et al, 2019;Rezaei et al, 2016), which produce a similar kind of rash and fever.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, the identification of ancient B19V in a Colonial context is noteworthy considering several recent reports reveal that measles-like cases were actually attributable to B19V (De Los Ángeles Ribas et al, 2019;Rezaei et al, 2016) or rubella (Anderson et al, 1985;Davidkin et al, 1998;De Los Ángeles Ribas et al, 2019;Rezaei et al, 2016), which produce a similar kind of rash and fever.…”
Section: Discussionmentioning
confidence: 95%
“…1 Erythema infectiosum is often mistakenly diagnosed as measles or rubella. [2][3][4] In Belarus, during the final stages of measles and rubella elimination between 2009 and 2011, 26.2% of suspected measles or rubella cases were B19V-positive compared with 6.1% for measles and 2.6% for rubella. 2 In Cuba, where measles and rubella had been eliminated, B19V infection was confirmed in 10.7% of patients with fever-rash illness and none were diagnosed with measles or rubella.…”
Section: Introductionmentioning
confidence: 99%
“…This study included in the non-rubella panel, sera collected from confirmed cases of other viral agents that may present with symptoms similar to that of rubella (fever and rash). Sera from these cases may be subjected to rubella IgM testing as part of the differential diagnosis strategy or captured through case finding algorithms (7,8,(11)(12)(13)(14)(15). The Serion ELISA method in particular was prone to cross-reactivity with sera from cases of dengue, measles and parvovirus B19.…”
Section: Discussionmentioning
confidence: 99%
“…A panel of 238 sera was assembled that included in the non-rubella panel, sera IgM positive for chikungunya, dengue, measles, parvovirus B19, roseola and zika viruses. These viruses were chosen because they can also present with fever and rash symptoms and thus may be captured in rubella testing algorithms during differential diagnosis or active case finding (7,8,(11)(12)(13)(14)(15). Some, such as parvovirus B19, have been previously noted to be a source of cross-reactivity with methods for the detection of anti-rubella IgM antibody (16).…”
Section: Introductionmentioning
confidence: 99%